Assessment of STI screening in Romania using a multiplex PCR technique - Alecsandra Iulia Grad; Mihaela Laura Vica; Loredana Ungureanu; Costel Vasile Siserman; Alexandru Dumitru Tătaru; Horea Vladi Matei (Journal of Infection in Developing Countries)
Introduction: Most sexually transmitted infections (STIs) are curable, but inappropriate treatment can lead to serious complications. The importance of setting up STI screening programs has been highlighted in various studies, the absence of such national programs accounting for the lack of STI statistics in Romania. The purpose of our study was to evaluate multiplex PCR as a screening method for the most common 6 STIs and establish their frequency in a group of symptomatic and asymptomatic patients. We aimed to highlight STI associations and correlations between STI pathogens and symptomatology, demographic status, antecedents or sexual partners.